Procalcitonin as a Biomarker in Severe Acute Respiratory Infections in Children: A Clinical Study - Sangle, Dhananjay Arvind (Journal of Biomedical and Pharmaceutical Research, 2018)
Background: Severe acute respiratory infections (SARIs) in children pose significant health challenges and can lead to serious complications. Accurate and timely differentiation between bacterial and viral infections is crucial for appropriate management. Procalcitonin (PCT) has emerged as a promising biomarker for this purpose. Objective: This study aims to evaluate the role of procalcitonin levels in differentiating bacterial from viral infections in children with severe acute respiratory infections. Material and Methods: A total of 60 pediatric patients diagnosed with SARIs were included in this prospective study conducted in the Department of Pediatrics at a tertiary care hospital. PCT levels were measured upon admission, and clinical parameters were assessed. Patients were categorized based on their diagnosis: bacterial or viral infection. Results: The study found significantly higher procalcitonin levels in children with bacterial infections compared to those with viral infections, indicating PCT’s utility as a biomarker for guiding treatment decisions. Conclusion: Procalcitonin is a valuable biomarker in managing severe acute respiratory infections in children, aiding in the differentiation between bacterial and viral infections. Keywords: Procalcitonin, Severe Acute Respiratory Infections, Children, Biomarker, Pediatrics.